Ordering disorder : grid principles for web design. /. - Vinh, Khoi, ....- (Berkeley : New Riders, 2011)
The grid has long been an invaluable tool for creating order out of chaos for designers of all kinds--from city planners to architects to typesetters and graphic artists. In recent years, web designers, too, have come to discover the remarkable power that grid-based design can afford in creating intuitive, immersive, and beautiful user experiences. "Ordering Disorder" delivers a definitive take on grids and the Web. It provides both the big ideas and the brass-tacks techniques of grid-based design. Readers are sure to come away with a keen understanding of the power of grids, as well as the design tools needed to implement them for the World Wide Web. Khoi Vinh is internationally recognized for bringing the tried-and-true principles of the typographic grid to the World Wide Web. He is the former Design Director for NYTimes.com, where he consolidated his reputation for superior user experience design. He writes and lectures widely on design, technology, and culture, and has published the popular blog Subtraction.com for over a decade. More information at grids.subtraction.com